Bearish/Inverse RSI Indicator RSIB by Modifying Traditional RSI Indicator to Obtain a Customized Indicator for Stock Market Price Forecasting - Balatripurasundari, K. (Indian Journal of Research in Capital Markets, 2025)
Purpose : The study aimed to analyze the core concept underlying the stock market technical indicator relative strength index (RSI), identify its strengths and limitations, and develop an alternative indicator more suitable for bearish market conditions. This new indicator is termed RSIB (Bearish RSI), functioning as an inverse or conjugate of the traditional RSI. Methodology : Technical, fundamental, and quantitative analyses were used in stock market trading. Fundamental analysis assessed intrinsic asset value based on macroeconomic indicators, such as interest rates and inflation, alongside the company’s business model. The technical analysis utilized historical stock returns, price fluctuations, chart patterns, and technical indicators to guide buy and sell trading decisions. Quantitative analysis involves examining company balance sheets against industry benchmarks. This research employed technical analysis, specifically exploring the RSI indicator’s formula. By dissecting and modifying the RSI to focus on its average gains and losses components, the study formulated the RSIB indicator. Historical closing prices from four actively traded stocks and one National Stock Exchange (NSE) index were analyzed to compute RSIB. Findings : Plotting RSIB alongside RSI introduced a novel visual analytical approach, enhancing stock price movement analysis. Buy and sell signals emerged clearly at crossover points between RSI and RSIB, significantly improving the indicator’s forecasting capability. Practical Implications : The study recommended plotting RSIB with traditional RSI for efficient visual analytics and decision-making. While acknowledging limitations, the findings offered scope for further research across broader markets. Originality : This research uniquely revisited and modified the RSI concept to enhance its effectiveness during bearish market phases.